1971
DOI: 10.1111/j.1532-5415.1971.tb02580.x
|View full text |Cite
|
Sign up to set email alerts
|

Haloperidol Versus Thioridazine for Hospitalized Psychogeriatric Patients: Double‐blind Study*

Abstract: A 12‐week double‐blind study was started with 60 actively psychotic geriatric patients residing in Boston State Hospital, to compare the psychopharmacological efficacy of haloperidol with that of thioridazine. The dosage was flexible—an initial low dosage followed by gradual increments until a satisfactory therapeutic response was obtained. Average maintenance dosages were about 2 mg a day for haloperidol and 100–125 mg a day for thioridazine. The rating instruments used were the Brief Psychiatric Rating Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1973
1973
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…Double‐blind comparison trials of neuroleptic drugs have reported less consistently positive results. In diagnostically heterogeneous state hospital populations (including many patients with organic mental disorders), studies comparing haloperidol with thioridazine 26,27 and chlorpromazine with thioridazine 28 have reported that low doses of these drugs reduce symptoms of agitation, anxiety, irritability, and hostility. In demented nursing home patients with behavioral disturbances, haloperidol (average, 2 mg per day) and thioridazine (average, 107 mg per day) reduced symptoms such as anxiety, emotional withdrawal, tension, depressive mood, hostility, uncooperativeness, and excitement 29 .…”
Section: Neurolepticsmentioning
confidence: 99%
“…Double‐blind comparison trials of neuroleptic drugs have reported less consistently positive results. In diagnostically heterogeneous state hospital populations (including many patients with organic mental disorders), studies comparing haloperidol with thioridazine 26,27 and chlorpromazine with thioridazine 28 have reported that low doses of these drugs reduce symptoms of agitation, anxiety, irritability, and hostility. In demented nursing home patients with behavioral disturbances, haloperidol (average, 2 mg per day) and thioridazine (average, 107 mg per day) reduced symptoms such as anxiety, emotional withdrawal, tension, depressive mood, hostility, uncooperativeness, and excitement 29 .…”
Section: Neurolepticsmentioning
confidence: 99%
“…The literature on the pharmacological management of symptoms commonly associated with delirium includes an early series of controlled intervention trials that compared haloperidol and thioridazine (20)(21)(22) and thioridazine and diazepam (23) in the treatment of "agitation and psychotic" symptoms related to dementia (often with superimposed delirium) in geriatric populations. Two additional controlled trials compared haloperidol and droperidol (24) in "agitated and combative" emergency room patients with a variety of undefined organic mental disorders and functional disorders, and paraldehyde and diazepam (25) in medically hospitalized patients with alcohol withdrawal and "delirium tremens."…”
mentioning
confidence: 99%
“…Although the parenteral route permits more rapid therapeutic effects, it also may increase the potential for side effects. The extrapyramidal reactions often associated with haloperidol therapy are infrequent and mild at low dosage levels (7, 10). In this trial, extrapyramidal reactions did not occur in any patient treated with the therapeutically effective 1.0‐mg dose of haloperidol injected intramuscularly.…”
Section: Discussionmentioning
confidence: 99%